Fire Tracking and Suppression Mobile Robot - Design and Construction - Abdülkadir ÇAKIR; Aqeel bahaa BADRI (Institute of Advanced Engineering and Science, 2017)
Robots is one of the most important devices in the world that work automatically without human intervention. Robot can work for long hours without feeling tired and can be performed work that can be dangerous to human life. Autonomous robots are used today in many areas in our daily lives, for example, industry, Agriculture, Health, Education, scientific explorations and many other fields. Therefore in this research we will going to design autonomous robot that able to find and extinguish fires. In some cases, the dense flames very dangerous to humans live and therefore require intervention of robot. Fire tracking and suppression robot is a robot can automatically find and fighting fire. In this project a camera and flame sensor based on an rotary base was used. It can detect fire in an angle of rotation of 1600. ATmega328 microcontroller based on Arduino Uno board have been used, to control the robot to do the right work without mistakes, ATmega328 based on Arduini Uno board have been used, and it can be programmed using C language by using arduino IDE.